(untitled) (Malaysian Management Journal, 2012)
This study intends to investigate the relationships of technical quality, functional quality, communication effectiveness, and trust with relationship commitment in the context of the subscribers of the leading WiMax internet service provider (WISP) in Bangladesh. It presents a critical appraisal of a few important antecedents of subscribers’ relationship commitment, which eventually engenders customer loyalty. Data were collected from 172 subscribers by using a survey via the personal interview technique. Later, correlation analysis and stepwise multiple regression were carried out. All the inter-construct correlations were found to be strong and supported the hypothesized relationships with high statistical significance. In the third model identified from the stepwise multiple regression, three out of four hypotheses got supported empirically. The stepwise regression results revealed that technical quality, trust, and communication effectiveness are the significant and powerful predictors of relationship commitment respectively. Functional quality did not appear to be a statistically significant predictor of relationship commitment. A clear understanding of such important precursors of subscribers’ relationship commitment might encourage the service provider(s) to indentify the needful and take necessary measures to strengthen subscribers’ relationship commitment to create a loyal customer base.